2002
DOI: 10.2307/3069621
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Performance Incentives and Student Outcomes

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…Instructional leaders focus primarily on improving students' academic output by making the strategies and activities of the school compatible with the academic mission of the school. The positive effect of instructional leadership on student achievement is supported by the literature (Eberts et al 2002;Hallinger et al 1996a, b;Lee et al 2012;O'Donnell and White 2005;Valentine and Prater 2011). When the findings of leadership style moderator are examined as a whole, it is observed that instructional leadership has a weaker effect.…”
Section: Discussionsupporting
confidence: 58%
“…Instructional leaders focus primarily on improving students' academic output by making the strategies and activities of the school compatible with the academic mission of the school. The positive effect of instructional leadership on student achievement is supported by the literature (Eberts et al 2002;Hallinger et al 1996a, b;Lee et al 2012;O'Donnell and White 2005;Valentine and Prater 2011). When the findings of leadership style moderator are examined as a whole, it is observed that instructional leadership has a weaker effect.…”
Section: Discussionsupporting
confidence: 58%
“…Usually the identification strategy is that there has been a reform which generates a form of quasi-experimental change in teacher remuneration. Papers by Lavy (2002), Ballou (2001), Eberts et al (2002), Figlio and Kenny (2007) and Atkinson et al (2004) in a variety of contexts show some degree of relationship between performance pay and positive student outcomes.…”
Section: The Link Between Teacher Wages and Pupil Outcomesmentioning
confidence: 95%
“…Numerous analyses show that civil servants and public-sector employees are not comfortable with NPHRM (Light 2002;Soni 2004;Farnham 2003). Performance-related pay has also shown its limits in many public (Pearce et al 1985;Marsden and Richardson 1994;Eberts et al 2002) and private (Igalens and Roussel 1999) contexts. The modernization of HRM is increasingly calling into question the traditional fundamental values of public organizationsequality, integrity, continuity, caution and neutrality -and proposing new values, such as efficiency, flexibility, innovation, risk and change, which are often contrary to those traditional values.…”
Section: The New Public Hrmmentioning
confidence: 98%